The Gateway to Computer Science Excellence
0 votes
38 views
Consider the nonhomogeneous linear recurrence relation $a_n$=$3a_{n-1}$+$2^n$

in the book solution is given $a_n$=$-2^{n+1}$

but I’m getting $a_n$=$3^{n+1}-2^{n+1}$
in Combinatory by Active (5.1k points)
edited by | 38 views
0
what is the base condition ?
$-2^{n+1}$ is the particular solution..
+1
base condition is $a_0$=1
im getting the same

homogeneous part i got $3^{n+1}$
and particular part $-2^{n+1}$
+1

@aditi19

your answer is correct. 

You can verify yourself by taking small values of 'n'. 

For eg.,  for $n=1$, recurrence relation gives $a_1=3a_0+2^1=3*1+2=5$

Now,$-2^{n+1}$ will give answer as $-2^2=-4$ where as $3^{n+1}-2^{n+1}$ will give answer as $3^2-2^2=5$. So, your answer is correct. 

Please log in or register to answer this question.

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,645 questions
56,542 answers
195,693 comments
101,539 users